Dynamic S-box implementation in PRESENT Cipher - Anurupam, Kumar (International Journal of Computer Sciences and Engineering, 2018)
Lightweight cryptography is a very promising cryptographic technique which focuses on providing security to the smart devices in the IOT environment. The devices used in the IOT environment generate a large amount of data which can be very critical and sensitive to us. These IOT devices are generally very small and require low power to operate. So implementing strong cryptographic algorithms which need high computation is very difficult because of these limitations. Many lightweight ciphers are developed which focused on providing efficient encryption in these resource sensitive environment without taking much computational power. These ciphers are based on different approaches like AES, Feistel networks. In this paper it is proposed to make some change in the design of one such lightweight cipher i.e. PRESENT. The PRESENT cipher is based on the Substitution Permutation network and utilizes the S-box during the encryption. Here, the motivation is to improve the cipher technique and increase its efficiency by creating the dynamic S-boxes and comparing it with the static S-box on various factors.